Ordinance no. 11-An Ordinance Concerning Offenses and Disorderly Conduct, § 51, Ilwaco Town Council (1891) (Washington). - (:unkn) unknown (My University, 1891)
If any person shall carry consealed or about his person or carry upon his person while xxxxxxxxxxx3 in a stete of intoxication, or while under the influence of alcoholic liquors any pistol, revolver, dirk, dagger, slungshot, knuckles of metals or other deadly weapons shall be deemed guilty of a misdemeanor and upon conviction thereof before the Police Court shall be fined not less than Five nor more than One Hundred dollars. Provided that nothing being contained shall prevent a police officer or any officer or person whose duty it is to execute process or warrants or to suppress breaches of the peace or to make arrests from carrying such weapons in the necessary discharge of his duty."
Keywords: CARRY - CONCEALED